FOTOPERIODE DAN PEMBUNGAAN TANAMAN - Sutoyo Sutoyo (Universitas Tribhuwana Tunggadewi, 2011)
Photoperiod is the relative ratio between the length of time during the night. The response is the development of the plant against photoperiod called photoperiodism. Vegetative growth that is affected is the formation of bulbs and tubers, branching, leaf shape, the formation of pigment, hair formation, root development, seed dormancy and death. Reproductive growth is influenced by photoperiod is the formation of flowers, fruits and seeds. Flowering in plants is influenced by three factors: photoperiod, phytochrome and the biological rhythms of plants. Knowledge of plant responses to photoperiod can be used (1) selection of the plant before it is introduced into a region need to be tailored to the requirements photoperiod area, (2) artificial irradiation is widely used in horticultural plants to control flowering season and to increase the yield of plants in greenhouses, and (3) artificial light can allow cross it flowerence different plants that season when the natural conditions